Investigación de mercados emergentes para la exportación de café Tolimense (2022)
This paper analyzes is focused on diversifying the export destinations of Tolima’s coffee, looking for internationalization alternatives in emerging markets that are positioned as potential niches to develop eventual export processes of Tolima’s coffee, according to the dynamics of international trade, based on the analysis of different market variables that allow identifying target markets.